stx(1c) Is the Most Common Shiga Toxin 1 Subtype among Shiga Toxin-Producing Escherichia coli Isolates from Sheep but Not among Isolates from Cattle - Brett, Kim N. (American Society for Microbiology, 2003)
Unlike Shiga toxin 2 (stx(2)) genes, most nucleotide sequences of Shiga toxin 1 (stx(1)) genes from Shiga toxin-producing Escherichia coli (STEC), Shigella dysenteriae, and several bacteriophages (H19B, 933J, and H30) are highly conserved. Consequently, there has been little incentive to investigate variants of stx(1) among STEC isolates derived from human or animal sources. However stx(1OX3), originally identified in an OX3:H8 isolate from a healthy sheep in Germany, differs from other stx(1) subtypes by 43 nucleotides, resulting in changes to 12 amino acid residues, and has been renamed stx(1c). In this study we describe the development of a PCR-restriction fragment length polymorphism (RFLP) assay that distinguishes stx(1c) from other stx(1) subtypes. The PCR-RFLP assay was used to study 378 stx(1)-containing STEC isolates. Of these, 207 were isolated from sheep, 104 from cattle, 45 from humans, 11 from meat, 5 from swine, 5 from unknown sources, and 1 from a cattle water trough. Three hundred fifty-five of the 378 isolates (93.9%) also possessed at least one other associated virulence gene (ehxA, eaeA, and/or stx(2)); the combination stx(1), stx(2), and ehxA was the most common (175 of 355 [49.3%]), and 90 of 355 (25.4%) isolates possessed eaeA. One hundred thirty-six of 207 (65.7%) ovine isolates possessed stx(1c) alone and belonged to 41 serotypes. Seventy-one of 136 (52.2%) comprised the common ovine serotypes O5:H(−), O128:H2, and O123:H(−). Fifty-two of 207 isolates (25.1%) possessed an stx(1) subtype; 27 (51.9%) of these belonged to serotype O91:H(−). Nineteen of 207 isolates (9.2%) contained both stx(1c) and stx(1) subtypes, and 14 belonged to serotype O75:H8. In marked contrast, 97 of 104 (93.3%) bovine isolates comprising 44 serotypes possessed an stx(1) subtype, 6 isolates possessed stx(1c), and the remaining isolate possessed both stx(1c) and stx(1) subtypes. Ten of 11 (91%) isolates cultured from meat in New Zealand possessed stx(1c) (serotypes O5:H(−), O75:H8/H40, O81:H26, O88:H25, O104:H(−)/H7, O123:H(−)/H10, and O128:H2); most of these serotypes are commonly recovered from the feces of healthy sheep. Serotypes containing stx(1) recovered from cattle rarely were the same as those isolated from sheep. Although an stx(1c) subtype was never associated with the typical enterohemorrhagic E. coli serogroups O26, O103, O111, O113, and O157, 13 human isolates possessed stx(1c). Of these, six isolates with serotype O128:H2 (from patients with diarrhea), four O5:H(−) isolates (from patients with hemolytic-uremic syndrome), and three isolates with serotypes O123:H(−) (diarrhea), OX3:H8 (hemolytic-uremic syndrome), and O81:H6 (unknown health status) represent serotypes that are commonly isolated from sheep.